APLIKASI PEMBELAJARAN YOGA HINDU BERBASIS ANDROID - kadek ardiago; Machudor Yusman; Wayan Rumite (Universitas Lampung, 2019)
Yoga , in Hindu philosophy, focuses on meditation activities or tapa where ones focuses all thoughts to control the five senses and the body as a whole. The rapid progress of information and communication technology and the lack of Hindu Yoga learning media in digital form have encouraged the development of Hindu Yoga Learning Applications Android-based. This application is expected to be a practical and interesting learning media to be learnt, as well as a reference in learning the movements of Hatha Yoga and Surya Namaskara besides books. This study has succeeded in developing an Android Application of Hindu Yoga Learning consisting of 46 Yoga movements, among others, 12 (twelve) Surya Namaskara movements, 8 (eight) pranayama movements, 7 (seven) sitting position of asanas movements, 8 standing position of asanas movements and 11 (eleven) sleep position of asanas movements. This application runs on the Android operating system so that it can be accessed by everyone and at any time on a smartphone or tablet computer that supports the Android operating system. The conclusion of this study is that the Hindu Yoga Learning Applications Android-based has been successfully built and it has been tested to match with the expected result.